Desempenho, comportamento e características de carcaça de bovinos terminados em confinamento com adição de óleo de cravo ou de canela na dieta - Ornaghi, Mariana Garcia (2016)
In feedlot cattle production system it is required to add compounds to modulate the rumen fermentation. In general, these substances are antibiotics or ionophores. However, these substances are banned in the European Union and the United States can be banned soon. Thus the development of non-invasive alternative substances in feed is necessary. So, natural substances have become the targets of various researches on the hole world. Among these substances, essential oils have attracted the spotlight. However, for its addition in feed is necessary to characterize the various plant products, and to know the mode of action of these substances. Essential oils have antimicrobial action, antioxidant, and antiviral, among other actions. Furthermore, essential oils have a wide range of human health effects, including positive effects on cardiovascular diseases, certain tumors, inflammatory processes, and generally diseases in which there is an uncontrolled proliferation of free radicals. This study aimed to evaluate the animal performance, carcass characteristics, temperament and ingestive behavior of 40 crossbred young bulls (½Brown Swiss - ½Nellore) 10 ± 2.2 month-old, average body weight of 219 ± 11.7 kg without addition or with different levels (3500 or 7000 mg/day/animal) of clove or cinnamon essential oils in the diets.The finishing period in feedlot was 187 days. Animal performance was significantly higher for the group supplemented with clove (both levels) than control group without supplementation. Dry matter feed intake and other nutrients were higher for young bulls supplemented with essential oils in the diets than control group and similar between young bulls fed any essential oils or dosage level. Feed efficiency was similar among five diets, as well as digestibility in vitro. Still, addition of clove or cinnamon essential oil did not alter temperament and ingestive behavior of young bulls. Time spent for water ingestion ruminating, feeding and idle was similar between diets. Cold carcass weight was higher for clove groups than control group. However, carcass weight was similar between young bulls supplemented with clove or cinnamon. Muscle, fat, bone percentages and fat thickness, marbling, Longissimus muscle area and pH24 did not differ between diets. Results indicate that essential oils may improve animal performance of young bulls finished in high concentrate diets, without alter carcass characteristics and animal behavior.